Study of clinical spectrum of hyperbilirubinemia with frequency of glucose six phosphate dehydrogenase deficiency in neonates - Goel, Keshawati; Srivastava, Anshuman (International Journal of Research in Medical Sciences, 2021)
Background: Jaundice is defined as visible reflexion of serum hyperbilirubinemia on mucous membranes and skin as yellowish discoloration. The frequency of icterus among neonates is about 1 in 2500-5000 live births. When there is disparity between the production of bilirubin, conversion from unconjugated to conjugated bilirubin and excretion of bilirubin results in jaundice. Unconjugated bilirubin is usually harmless but it can also cross blood-brain barrier causing neurotoxicity or kernicterus. Methods: A hospital based prospective observational study which is carried out in the department of paediatrics of Teerthanker Mahaveer Medical College, Moradabad, Uttar Pradesh from December 2019 to November 2020 on 74 neonates who required admission for hyperbilirubinemia. Results: The most common jaundice occurred in neonates were idiopathic or breastfeeding jaundice as the neonates were breast fed (47.29%). The second most common cause was ABO incompatibility leading to jaundice in 27 (36.48%) neonates. Incidence of neonatal Sepsis, G6PD deficiency, hypothyroidism and cephalhematoma was 22.9%, 4.1%, 2.70% and 4.1% respectively. Polycythemia contributed to 1.35% and the frequency of hyperbilirubinemia in infants of diabetic mother’s or GDM was 10.8%. Rh incompatibility was seen in 13.5%. Conclusions: G6PD deficiency is a significant cause for NNHB and the cases with pathological jaundice if left untreated may lead to severe neurological deficits and lifelong disabilities, hearing impairment, mental retardation, seizures and movement disorders. Hence we recommend G6PD screening in every newborn with significant hyperbilirubinemia to reduce morbidity and mortality.